APPLICATION OF LAPAROSCOPIC LIFTING SYSTEMS IN PATIENTS WITH HIGH CARDIORESPIRATORY RISK - A. G. Khitar’Yan; I. A. Miziev; M. E. Provotorov; K. S. Veliev; E. E. Glumov; S. A. Kovalev; M. Kh. Abramyants; S. T. Khubiev (Вестник хирургии имени И.И. Грекова, 2016)
Intra-abdominal hypertension during laparoscopic operations increased the risk of complications from cardiovascular and respiratory systems. An application of laparolifting systems allowed doctors to avoid changes of pneumoperitoneum, although it was associated with technical difficulties in operation performance. The authors used a test in order to determine cardiorespiratory reserve in preoperative period. The reserve was characterized by decrease of stroke volume of the heart against the background of intra-abdominal hypertension. There was noted a reliable increase of complication rate in these patients in case of application of standard laparoscopic operation compared with operation using lifting systems.